2015
DOI: 10.1155/2015/196148
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory and Brainstem Auditory Evoked Potentials Assessed between 4 and 7 Days after Severe Stroke Onset Predict Unfavorable Outcome

Abstract: Our objective was to explore the best predictive timing of short-latency somatosensory evoked potentials (SLSEP) and brainstem auditory evoked potentials (BAEP) for unfavorable outcomes in patients with early stage severe stroke. One hundred fifty-six patients with acute severe supratentorial stroke were monitored according to SLSEP, BAEP, and the Glasgow Coma Scale (GCS) at 1–3 days and 4–7 days after the onset of stroke. All patients were followed up for outcomes at 6 months after onset using the modified Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…To eliminate the influence of impairment of the somatosensory pathway from the spinal cord (SC) to the thalamus and somatosensory cortex on the N30 SEP status, this study examined the correlations between N30 and the other indexes mentioned above among 33 patients positive for the presence of N20/P25 SEPs ( 21 ). The results indicate that when the somatosensory pathway from the SC to the thalamus was present, the patients who were N30 SEP absent presented higher levels of muscle tone than those who were N30 SEP positive ( U = 51, p < 0.01) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the influence of impairment of the somatosensory pathway from the spinal cord (SC) to the thalamus and somatosensory cortex on the N30 SEP status, this study examined the correlations between N30 and the other indexes mentioned above among 33 patients positive for the presence of N20/P25 SEPs ( 21 ). The results indicate that when the somatosensory pathway from the SC to the thalamus was present, the patients who were N30 SEP absent presented higher levels of muscle tone than those who were N30 SEP positive ( U = 51, p < 0.01) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The evoked potentials were calculated by averaging the recordings at every 500 stimuli, and the responses were filtered with a bandpass filter from 3 to 30 Hz ( 20 ). The existence of N30 and N20 SEPs was defined as potentials within 3 SD of the mean value of the normal data from the healthy side ( 21 ). Outside of this range, the absence of SEPs was defined (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenic mechanisms for recording of abnormal potentials include cortical depression and diaschisis. 20,21 Zhang et al 7 also reported that N20 of SSEP and wave V of BAEP after 4 to 7 days of stroke onset better predict the stroke outcome. Tzvetanov and Rousseff 22 found that median nerve SSEP had an independent predictive value in the functional recovery, while the combined assessment of median nerve SSEP and Medical Research Council scale improved the prognosis in acute stroke.…”
Section: Discussionmentioning
confidence: 98%
“…6 Literature describes early prognosis may also improve the treatment strategies of stroke. 7 Somatosensory evoked potentials (SSEPs) and brain stem auditory evoked potentials (BAEPs) are the useful, noninvasive means of assessing somatosensory and auditory system functioning. 2 8 Previous studies also reported that short-latency SSEPs N20 and BAEP wave V within 7 days of stroke were highly consistent with the patient outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation